Legal Protection for Consumers Due to Breach of Contract by Business Operators in Electronic Transactions (Case Study Of Harizqi Azri and Juni Fairnando) - Nadia Mardesya; Richard Candra Adam (UNES Law Review, 2023)
Electronic transactions refer to the process of buying and selling goods and services over the Internet. With the presence of electronic transactions, it has become much easier to engage in various transactions. However, there are still many parties with the intention of committing crimes. Therefore, there is a need for legal protection for consumers in electronic transactions. The legal protection for consumers is regulated by Law Number 8 of 1999 concerning Consumer Protection (UUPK). The common violations committed by business actors involve the infringement of Article 4 of the UUPK, which pertains to consumer rights. Consumers experience losses and breaches of contracts due to the exploitation of situations by business actors. In addition to the UUPK, in electronic transactions, consumer protection is also regulated by Law Number 11 of 2008 concerning Electronic Information and Transactions (ITE). Consumer protection, as explained in Article 1, Number 1 of the UUPK, emphasizes that all efforts are made to ensure legal certainty in order to provide protection for consumers.